Assessing the significance of endemic disease in conservation—koalas, chlamydia, and koala retrovirus as a case study. Issue 4 (28th November 2017) - McCallum, Hamish; Kerlin, Douglas H.; Ellis, William; Carrick, Frank
Abstract: It can be difficult to establish the conservation significance of endemic infectious diseases—those that are well established in a population—in contrast with infectious diseases that are still invading. This difficulty can have important implications for designing policy to address species declines. The infectious diseases of koalas provide an ideal case study to examine issues involved in identifying the role of endemic disease in conservation biology. Koala populations are in decline, amidst claims for many years that infectious diseases, particularly those with chlamydial etiology, play a key role in this loss. However, weak associations between prevalence of infection, clinical signs of disease, and population decline mean that it remains unclear whether infectious disease is a primary driver of koala population decline. There are multiple causes of koala decline including drought, habitat destruction, and disease. Well‐designed experiments, linked to appropriate models, are necessary to determine the true role of infectious disease in the current koala population declines and whether a focus on disease is likely to be a feasible, let alone the most cost‐effective, means of preventing further declines.